2014 Multiple Sclerosis Therapeutic Update. (April 2014) - Cree, Bruce A. C.
Rapid advances are occurring in multiple sclerosis disease modifying therapies. Recent therapeutic advances include modifications to improve tolerability of existing products (e.g. interferon beta and glatiramer acetate), development of novel anti-neuroinflammatory medications (e.g. fingolimod, teriflunomide and dimethyl fumarate, daclizumab, alemtuzumab, ocrelizumab) and investigation of treatments in progressive MS (e.g. natalizumab, mastinib, natalizumab, siponimod). The impact of vitamin D supplementation on the disease course in relapsing MS patients is also being studied in several clinical trials. This article reviews the current state of the field with a forward look to the next phase of MS research that could focus on strategies to promote remyelination and provide neuronal protection.